Nomen est omen : medical and pharmaceutical occupations in Slovenian family names = Nomen est omen : medicinska i farmaceutska zanimanja u slovenskim prezimenima - Ramšak, Mojca (Array, 2020)
The heritage of Slovenian house names and surnames reflects, among others, the former medicine and pharmaceutical occupations, midwifery, and folk medicine practices, and besides that, also health status and illnesses of people. Surnames, which are especially strongly intertwined with family, local and social history, are closely related to folk medicine and magic. Unlike house names (vulgo), which are the usual nicknames for physical and mental characteristics and abilities, surnames denote medicals occupations and medicinal folk practice as such. According to the most recent data (as of January 1, 2020) of The Statistical Office of the Republic of Slovenia, at least 40 surnames reminiscent former medical or pharmaceutical professions. These newly discovered digital data in open access are precious for the history of medicine because they allow comparing surnames geographically, by frequency, and through the time.